Cross-cultural approaches to the study of alcohol : an interdisciplinary perspective - Everett, Michael W.; Waddell, Jack O., 1933-; Heath, Dwight B. (World anthropology., 1976)
Examines the relationship between alcohol studies and the cross-cultural perspective of anthropology.